El sistema inmune innato I: sus mecanismos - Collado, Victorio M.; Porras, Rebeca; Cutuli, Mª Teresa; Gómez-lucía , Esperanza (Revista Complutense de Ciencias Veterinarias, 2008)
The innate immune system emerged very early in the evolution and, with few variations, defends most animals from the external aggressions, although usually the adaptive immunity receives more attention. In this review several of aspects of the innate immune system are revised, such as the similarities and differences between the innate and adaptive immune systems, the recognition of the pathogens, and the mechanisms that are triggered to eliminate them, which start with the activation of complement that shoots a series of responses, and phagocytosis, which also improves with complement activation. In addition, the innate immune system has evolved to collaborate with the acquired immunity. Without this collaboration most of the antibodies would not be formed, or the so called cellular base immunity would not occur. In conclusion, the innate immune system is a fundamental pillar for maintaining the integrity of the organism.